Antarctic Snow Radar-Derived Relative Accumulation Product - Marissa Dattler; Jan Lenaerts; Brooke Medley (Zenodo, 2019)
Small-scale Antarctic accumulation rates relative to MERRA-2 precipitation-evaporationas derived from NASA Operation IceBridge snow radar.